Cellular Fractionation and Nanoscopic X-Ray Fluorescence Imaging Analyses Reveal Changes of Zinc Distribution in Leaf Cells of Iron-Deficient Plants - Vigani, Gianpiero; Bohic, Sylvain; Faoro, Franco; Vekemans, Bart; Vincze, Lazlo; Terzano, Roberto (Frontiers in Plant Science, 2018)
Multilevel interactions among nutrients occur in the soil-plant system. Among them, Fe and Zn homeostasis in plants are of great relevance because of their importance for plant and human nutrition. However, the mechanisms underlying the interplay between Fe and Zn in plants are still poorly understood. In order to elucidate how Zn interacts with Fe homeostasis, it is crucial to assess Zn distribution either in the plant tissues and within the cells. In this study we investigated the subcellular Zn distribution in Fe-deficient leaf cells of cucumber plants by using two different approaches: cellular fractionation coupled with inductively coupled plasma mass spectrometry (ICP/MS) and nanoscopic synchrotron X-ray fluorescence imaging. Fe-deficient leaves showed a strong accumulation of Zn as well as a strong alteration of the organelles' ultrastructure at the cellular level. The cellular fractionation-ICP/MS approach revealed that Zn accumulates in both chloroplasts and mitochondria of Fe deficient leaves. Nano-XRF imaging revealed Zn accumulation in chloroplast and mitochondrial compartments, with a higher concentration in chloroplasts. Such results show that i) both approaches are suitable to investigate Zn distribution at the subcellular level and ii) cellular Fe and Zn interactions take place mainly in the organelles, especially in the chloroplasts.